Memahami Perilaku Konsumen Dengan Teori Regret - Faraz, Faraz (Unisia, 2018)
In the consumer decision-making both personally and institutionally not always maximize profits but often anticipate the unpleasant feeling that will be experienced. According Zeelenberg, van Dijk, Manstead and Plight (1998) unpleasant feelings that dominated the feeling of regret. Regret studies on consumer behavior is one of the important studies in this discipline called behavioral economics which is currently a trending topic. The purpose of this article is to understand consumer behavior based on the theory regret the hope of obtaining a more adequate explanation in understanding the phenomenon of consumer behavior.